Getting the best out of straw return: Interactions with tillage depth related to biotic and abiotic factors - Yanjun Zhang; Bruce Osborne; Shuina Dang; Changyan Wang; Yuge Ren; Junliang Zou (Soil and Tillage Research, 2026)

How the Traffic-Light nutrition label promotes healthier choices: evidence from online shopping and eye-tracking experiments in China - Luchen Huang; Yanjun Ren (Food Quality and Preference, 2026)

Model-based inference of monsoonal moisture from stalagmite and tree-ring δ18O - Qiang Li; Yifan Wu; Jiachuan Wang; Yu Liu; Yanjun Cai; Haiwei Zhang; Liangcheng Tan; Jingyao Zhao; Changfeng Sun; Huiming Song; Yang Xu; Yueer Li; et al. (Quaternary Science Reviews, 2026)

Ultrafast electrothermal stabilization of heavy metals in municipal solid waste incineration fly ash by flash Joule heating - Yingchao Liu; Wenjing Lu; Liwen Zhang; Yanjun Liu; Erkang Feng; Zhenyu Ren; Teng Wang; Mingyue Xu; Dongbei Yue; Bing Deng (Journal of Hazardous Materials, 2026)

Antioxidant and hypoglycemic effects of phenolic-rich extracts from Eleutherococcus senticosus fruits using deep eutectic solvents - Yanjun Ren; Lizhu Zhao; Xiongfei Luo; Zhonghua Tang (Food Chemistry, 2026)

The dual role of crop-livestock diversification in household nutrition security: Evidence from rural Ethiopia - Taye Melese Mekie; Luchen Huang; Yanjun Ren; Tadie Mirie Abate (Food Policy, 2026)

Greener cities, cleaner homes: Evaluating the effect of China's low-carbon city pilot policy on urban household energy consumption structure - Yunchang Wang; Yanjun Ren; Jieyu Yang; Mi Zhou; Qiran Zhao (Energy Policy, 2026)

The effect of environmental concern on consumers’ preferences for carbon-neutral-labeled dairy: Evidence from China - Qi Liu; Shaoting Li; Yanjun Ren; Jens-Peter Loy (Journal of Environmental Management, 2026)

Climate change mitigation policy and human health: Evidence from the forest farm carbon sink projects in China - Jian Liu; Yanjun Ren; Thomas Glauben; Zhanli Sun (Environmental Impact Assessment Review, 2026)

Does message framing affect sustainable seafood consumption? - Evidence from eye-tracking experiments on ASC and organic-labeled products - Shihang Zhen; Yanjun Ren; Ivan Duric (Aquaculture, 2026)

SIRT1 protects against UVA-induced photoaging by suppressing oxidative stress and FOXO3a acetylation in human dermal fibroblasts - Wenjuan Ma; Min Jiang; Jingtao Zhang; Wenjie Liu; Yanjun Dan; Wenjia Sun; Li Ma; Leihong Xiang; Jie Ren (Journal of Photochemistry and Photobiology B: Biology, 2026)

The formation mechanism, analysis strategies, and regulation measures of gellan gum-based films: A review - Jiayuan Liang; Mingjing Yao; Yupeng Nie; Fan Xie; Zhiqiang Xiong; Guangqiang Wang; Yanjun Tian; Lianzhong Ai; Xuebing Ren (Carbohydrate Polymers, 2026)

Does refrigerator ownership improve household food security for rural residents? Evidence from longitudinal survey data in China - Luchen Huang; Yanjun Ren (Journal of Rural Studies, 2025)

Tyro3 upregulation is associated with muscle involvement in patients with idiopathic inflammatory myopathies - Huan Liu; Ying Ren; Qianwei Li; Yanjun Si; Yuehong Chen; Min Dong; Geng Yin; Qibing Xie (Immunologic Research, 2025)

Do forestry carbon sinks projects affect grain production? Evidence from China - Yuan Hu; Yanjun Ren; Thomas Glauben; Liangzhi You; Hongxing Lan; Weizhong Zeng (Food Security, 2025)

Fe/Fe3O4/FexN@N-doped porous carbon aerogels with superior electromagnetic attenuation performance and multifunctional applications - Yumei Ren; Zhen Qin; Tong Xi; Shuai Yang; Ziran Du; Desheng Feng; Zhongyi Bai; Yanjun Zheng; Xiaoqin Guo; Biao Zhao (Chemical Engineering Journal, 2025)

Effect of Attribute Information of Recycled Water on Willingness to Accept: Evidence from an Event-Related Potential (ERP) Experiment - Hanliang Fu; Bo Dong; Zhifang Wu; Caixia Hou; Yanjun Ren (Water Resources Management, 2025)

Identifying omitted high reactive VOCs emission sources in China based on new speciated emission inventory - Di Wang; Jinhong Du; Li Yang; Jinmin Zhao; Xinmin Zhang; Zhihao Zhang; Wenjuan Zhao; Weiqi Zhang; Yuzhe Zhang; Jinghua Ma; Wenjing Jin; Yanjun Ren; et al. (Journal of Cleaner Production, 2025)

Unlocking the potential of cotton-derived carbon aerogel for uranium extraction from real radioactive wastewater: A path to amidoxime and polyguanidine modification - Yang Wang; Yun Wang; Qi Ren; Zihao Feng; Yang Li; Yanjun Du; Xiaoyan Li; Yan Liu; Dingzhong Yuan; Tu Lan (Chemical Engineering Journal, 2025)

Inspiring the potential of graphene oxide aerogel for uranium(VI) electrosorption: A precursor reconfiguration strategy and synergistic integration with polyethyleneimine - Qi Ren; Yun Wang; Yang Wang; Zihao Feng; Yanjun Du; Changfu Wang; Yan Liu; Dingzhong Yuan; Hao Jiang; Yang Li (Desalination, 2025)

Altered functional connectivity within and between resting-state networks in ulcerative colitis - Yanjun Ren; Kaizhong Xue; Huijuan Xu; Lijie Hao; Quchuan Zhao; Tianyu Chi; Hongwei Yang; Xiaojing Zhao; Defeng Tian; Huihong Zhai; Jie Lu (Brain Imaging and Behavior, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Lactic acid/tartaric acid-maltitol antibacterial activity against spoilage bacteria and prevention of yellowing and wilting in spinach and oilseed rape - Dengyi Ye; Jing Ren; Yanan Zhang; Xiyu Wang; Jiali Guo; Bing Li; Quanliang Li; Yanjun Chen; Ping Chen; Biying Zhang (Food Chemistry, 2025)

Utilization of cold-rolling oil sludge via iron ore sintering co-processing technology: A strategy for industrial-scale disposal of hazardous solid waste - Shengxuan Fan; Mengting Qin; Yong Chen; Jinchao Wei; Qian Li; Wenjie Ren; Ying Liu; Yi Wang; Yanjun Huang; Lei Zhang (Process Safety and Environmental Protection, 2025)

Consumer preferences for sugar-sweetened beverages: Evidence from online surveys and laboratory eye-tracking choice experiments - Yanjun Ren; Qi Liu; Guanzhang Wu; Jens-Peter Loy (Food Policy, 2025)

Establishment of a standardized daily behavior collection and analysis system for brain disease models of rhesus and cynomolgus monkeys and its application in autism spectrum disorder - Xiaofeng Ren; Huimin Wang; Xiaoman Lv; Yi Zhou; Yingyin Fan; Yanjun Yu; Christoph W. Turck; Yuhui Chen; Longbao Lv; Yingzhou Hu; Hao Li; Wenchao Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2024)
Complex brain diseases seriously endanger human health, and early diagnostic biomarkers and effective treatments are currently lacking. Due to ethical constraints on human research, establishing monkey models is crucial to address these issues. With the rapid development of technology, transgenic monkey models of a range of brain diseases, especially autism spectrum disorder (ASD), have been successfully established. However, to establish practical and effective brain disease models and subsequently apply them to disease mechanism and treatment studies, there is still a lack of a standard tool, i.e., a system for collecting and analyzing the daily behaviors of brain disease model monkeys. Therefore, with the goal of undertaking a comprehensive and quantitative study of behavioral phenotypes, we established a standard daily behavior collection and analysis system, including behavioral data collection protocols and a monkey daily behavior ethogram (MDBE) for rhesus and cynomolgus monkeys, which are the most commonly used non-human primates in model construction. Then, we used ASD as an application example after referring to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision (DSM-5-TR), which is widely used in clinical disease diagnosis to obtain ASD core clinical symptoms. We then established a sub-ethogram (ASD monkey core behavior ethogram (MCBE-ASD)) specifically for quantitative assessment of the core clinical symptoms of an ASD monkey model based on MDBE. Subsequently, we demonstrated the high reproducibility of the system.

Does risk preference matter to consumers’ willingness to pay for functional food: Evidence from lab experiments using the eye-tracking technology - Shihang Zhen; Xianli Xia; Luchen Huang; Yihan Cao; Hanliang Fu; Yanjun Ren (Food Quality and Preference, 2024)

Systems engineering of Escherichia coli for high-level l-alanine production - Yupeng Nie; Mingjing Yao; Guozheng Jiang; Yi Yang; Shenbiao Wang; Hui Xu; Jiayuan Liang; Xuebing Ren; Yanjun Tian (Food Bioscience, 2024)

A review of quantification methods for light absorption enhancement of black carbon aerosol - Yao Kong; Guorui Zhi; Wenjing Jin; Yuzhe Zhang; Yi Shen; Zhengying Li; Jianzhong Sun; Yanjun Ren (Science of The Total Environment, 2024)

Consumers' willingness to pay for carbon-labeled agricultural products and its effect on greenhouse gas emissions: Evidence from beef products in urban China - Xuan Chen; Shihang Zhen; Shaoting Li; Jieyu Yang; Yanjun Ren (Environmental Impact Assessment Review, 2024)

Separation and quantification of tire and road wear particles in road dust samples: Bonded-sulfur as a novel marker - Yifan Ren; Wenhui Li; Qi Jia; Yanjun Zhao; Chen Qu; Li Liu; Jiemin Liu; Chuandong Wu (Journal of Hazardous Materials, 2024)

Do carbon labels increase Chinese consumers’ willingness to pay for carbon-labeled agricultural products? - Yalin Xu; Botong Xian; Yanjun Ren; Yanan Wang; Liangming Lang; Bowen Wang (Journal of Cleaner Production, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Critical impact of pyrolysis temperatures on biochars for peroxymonosulfate activation: Structural characteristics, degradation performance and mechanism - Suyun Pei; Yanjun Zhao; Wenhui Li; Chen Qu; Yifan Ren; Yue Yang; Jiemin Liu; Chuandong Wu (Chemical Engineering Journal, 2023)

Effect of straw return on soil respiration in dryland agroecosystem of China: A meta-analysis - Yanjun Zhang; Junliang Zou; Bruce Osborne; Wei Dang; Yuxia Xu; Yuanyuan Ren; Shuina Dang; Lijuan Wang; Xi Chen; Yuan Yu (Ecological Engineering, 2023)

Identification of Fangchinoline as a novel autophagy inhibitor with an adjuvant of chemotherapy against lung cancer - Zhenyang Ren; Yue Song; Jinhuan Xian; Yuan Liao; Yujuan Zhan; Tingxiu Zhao; Huiqi Wang; Junbo Jiang; Mansi Xu; Yanjun Jiang; Xiaodong Liu; Xianli Wei; et al. (Toxicology and Applied Pharmacology, 2023)

Does forest farm carbon sink projects affect agricultural development? Evidence from a Quasi-experiment in China - Jian Liu; Yanjun Ren; Yu Hong; Thomas Glauben (Journal of Environmental Management, 2023)

Associations between congenital heart disease and air pollutants at different gestational weeks: a time-series analysis - Wenling Zhang; Yanjun Yang; Yanyan Liu; Li Zhou; Yan Yang; Li Pan; Yupei Ba; Ruijuan Wang; Yanbei Huo; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Geochemistry and Health, 2023)

Mapping China’s planted forests using high resolution imagery and massive amounts of crowdsourced samples - Kai Cheng; Yanjun Su; Hongcan Guan; Shengli Tao; Yu Ren; Tianyu Hu; Keping Ma; Yanhong Tang; Qinghua Guo (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Research on the effects of complex terrain on the hydrodynamic performance of a deep-sea fishlike exploring and sampling robot moving near the sea bottom - Gang Xue; Fagang Bai; Lei Guo; Pingshun Ren; Yanjun Liu (Frontiers in Marine Science, 2023)
Deep-sea exploring and sampling technologies have become frontier topics. Generally, the movable exploring mode near the seabed with low disturbance is an important way to improve the measurement accuracy and expand the measurement range. Inspired by fish, the fishlike propulsion method has the characteristics of low disturbance and high flexibility, which is very suitable for near-seabed detection under complex terrain conditions. However, the swimming mechanism and surrounding flow field evolution law of the robotic fish under the constraints of complex terrain are still unclear. In this paper, the confined terrain space is constructed with an undulating seabed and a narrow channel, and the hydrodynamic changing law and flow field evolution law of the autonomous swimming process of the fishlike swimmer in the confined space are analyzed. Moreover, the influence mechanism of the terrain on the motion performance of the robotic fish is revealed, and the optimal motion mode of the robotic fish under a complex terrain constraint is discussed. The results show that the propulsion force, Froude efficiency, and swimming stability of the robotic fish vary with the distance from the bottom under the undulating seabed condition lightly. When the distance from the bottom exceeds a certain value, it can be considered that the undulating seabed no longer affects the swimmer. Furthermore, when the robotic fish swims through a narrow channel with certain width, the swimming performance obviously varies with the distance from the boundary surface. During swimming in the confined terrain space, the propulsion force and swimming stability of robotic fish will decrease. In order to maintain the forward speed, the robotic fish should improve the tail-beat frequency in real time. However, considering the swimming stability, the tail-beat frequency is not the larger the better. The relevant conclusions of this paper could provide theoretical support for the development of low-disturbance bionic exploring and sampling platforms for deep-sea resources and environments.

The Critical Factors and Preventive Measures of Impoundment of Tailings Using Active Surface Subsidence Zones - Yang Liu; Yanjun Zhou; Rongxing He; Jianli Cao; Fengyu Ren; Fu Yu; Lu Yue (Geotechnical and Geological Engineering, 2023)

Association between air pollutants and neural tube defects during pregnancy in Lanzhou, China: a time series analysis - Yan Yang; Li Zhou; Wenling Zhang; Yanjun Yang; Yanyan Liu; Li Pan; Yanbei Huo; Ruijuan Wang; Yupei Ba; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Science and Pollution Research, 2023)

Elucidating the origin mechanism of a morphology-dependent layered double hydroxide catalyst toward organic contaminant oxidation via persulfate activation - Rongyao Wang; Yanjun Yu; Ruijuan Zhang; Xiaohua Ren; Weilin Guo (Environmental Science and Pollution Research, 2022)

Time series analysis on association between ambient air pollutants and orofacial clefts during pregnancy in Lanzhou, China - Yanyan Liu; Li Zhou; Wenling Zhang; Yanjun Yang; Yan Yang; Li Pan; Yupei Ba; Ruijuan Wang; Yanbei Huo; Xiaoyu Ren; Yana Bai; Ning Cheng (Environmental Science and Pollution Research, 2022)

Characteristics and Causes of Extreme Rainfall Induced by Binary Tropical Cyclones over China - Mingyang Wang; Fumin Ren; Yanjun Xie; Guoping Li; Ming-Jen Yang; Tian Feng (Asia-Pacific Journal of Atmospheric Sciences, 2021)
Binary tropical cyclones (BTC) often bring disastrous rainfall to China. From the viewpoint of the extreme of the BTC maximum daily rainfall, the characteristics of BTC extreme rainfall (BTCER) during 1960–2018 are analyzed, using daily rainfall data; and some representative large-scale mean flows, in which the associated BTCs are embedded, are analyzed. Results show that the frequency of BTCER shows a decreasing trend [−0.49 (10 yr) −1 ] and is mainly distributed within the BTC heavy rainstorm interval (100 mm ≤ BTCER

MiR-30a suppresses clear cell renal cell carcinoma proliferation and metastasis by targeting LRP6 - Yanjun Ren; Li Zhang; Wei Zhang; Yikai Gao (Human Cell, 2021)

Contamination assessment, health risk evaluation, and source identification of heavy metals in the soil-rice system of typical agricultural regions on the southeast coast of China - Yanjun Ren; Meng Lin; Qingming Liu; Zhonghao Zhang; Xufeng Fei; Rui Xiao; Xiaonan Lv (Environmental Science and Pollution Research, 2021)

Establishment of an Objective Standard for the Definition of Binary Tropical Cyclones in the Western North Pacific - Fumin Ren; Yanjun Xie; Biwen Yin; Mingyang Wang; Guoping Li (Advances in Atmospheric Sciences, 2020)

Design of Full-Ocean-Depth Self-Floating Sampler and Analysis of Factors Affecting Core Penetration Depth - Yugang Ren; Yanjun Liu; Zhongjun Ding; Baohua Liu; Jianhua Zhang (Journal of Ocean University of China, 2020)

Genome-wide association study of soybean seed germination under drought stress - Zhangxiong Liu; Huihui Li; Zuowang Gou; Yanjun Zhang; Xingrong Wang; Honglei Ren; Zixiang Wen; Beom-Kyu Kang; Yinghui Li; Lili Yu; Huawei Gao; Dechun Wang; et al. (Molecular Genetics and Genomics, 2020)

microRNA-499a promotes the progression and chemoresistance of cervical cancer cells by targeting SOX6 - Yibing Chen; Yucen Song; Yanjun Mi; Huan Jin; Jun Cao; Haolong Li; Liping Han; Ting Huang; Xiaofei Zhang; Shumin Ren; Qian Ma; Zhengzhi Zou (Apoptosis, 2020)

Biochar reduces cadmium accumulation in rice grains in a tungsten mining area-field experiment: effects of biochar type and dosage, rice variety, and pollution level - Min Zhang; Shengdao Shan; Yonggen Chen; Fang Wang; Deyi Yang; Jikai Ren; Haoyu Lu; Lifeng Ping; Yanjun Chai (Environmental Geochemistry and Health, 2019)

HOTAIR functions as a competing endogenous RNA to regulate PTEN expression by inhibiting miR-19 in cardiac hypertrophy - Yanjun Lai; Shuai He; Liming Ma; Hong Lin; Biyun Ren; Jing Ma; Xinyu Zhu; Shifang Zhuang (Molecular and Cellular Biochemistry, 2017)

Spatiotemporal analysis and risk assessment of thyroid cancer in Hangzhou, China - Xufeng Fei; Jiaping Wu; Qingmin Liu; Yanjun Ren; Zhaohan Lou (Stochastic Environmental Research and Risk Assessment, 2016)

Decrease in snowfall/rainfall ratio in the Tibetan Plateau from 1961 to 2013 - Jie Wang; Mingjun Zhang; Shengjie Wang; Zhengguo Ren; Yanjun Che; Fang Qiang; Deye Qu (Journal of Geographical Sciences, 2016)

The strong El Niño of 2015/16 and its dominant impacts on global and China's climate - Panmao Zhai; Rong Yu; Yanjun Guo; Qingxiang Li; Xuejuan Ren; Yaqiang Wang; Wenhui Xu; Yanju Liu; Yihui Ding (Journal of Meteorological Research, 2016)

Transgenic analysis reveals LeACS-1 as a positive regulator of ethylene-induced shikonin biosynthesis in Lithospermum erythrorhizon hairy roots - Rongjun Fang; Fengyao Wu; Ailan Zou; Yu Zhu; Hua Zhao; Hu Zhao; Yonghui Liao; Ren-Jie Tang; Tongyi Yang; Yanjun Pang; Xiaoming Wang; Rongwu Yang; et al. (Plant Molecular Biology, 2016)

Synthesis of α-Fe2O3 nanofibers for applications in removal and recovery of Cr(VI) from wastewater - Tongyan Ren; Ping He; Weiling Niu; Yanjun Wu; Lunhong Ai; Xinglong Gou (Environmental Science and Pollution Research, 2013)

β-Arrestin prevents cell apoptosis through pro-apoptotic ERK1/2 and p38 MAPKs and anti-apoptotic Akt pathways - Xiaohua Yang; Gengyin Zhou; Tao Ren; Hui Li; Yanjun Zhang; Deling Yin; Haixin Qian; Qinchuan Li (Apoptosis, 2012)

Nitric oxide enhances melanogenesis of alpaca skin melanocytes in vitro by activating the MITF phosphorylation - Yanjun Dong; Haidong Wang; Jing Cao; Jie Ren; Ruiwen Fan; Xiaoyan He; George W. Smith; Changsheng Dong (Molecular and Cellular Biochemistry, 2011)